1998
DOI: 10.1074/jbc.273.37.23844
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ATPase Activity of Purified Multidrug Resistance-associated Protein by Nucleoside Diphosphates

Abstract: Membrane vesicles prepared from cells expressing the multidrug resistance-associated protein (MRP) transport glutathione S-conjugates of hydrophobic substrates in an ATP dependent manner. Purified MRP possesses ATPase activity which can be further stimulated by anticancer drugs or leukotriene C4. However, the detailed relationship between ATP hydrolysis and drug transport has not been established. How the ATPase activity of MRP is regulated in the cell is also not known. In this report, we have examined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
6
32
0
Order By: Relevance
“…The R482 residue might, directly or indirectly, play a role in the coupling between energy supply and drug transport, and this effect would be altered upon mutation. A comparable activation or inhibition of ATP hydrolysis by modulators has been often reported for P-glycoprotein (42) and MRP1 (17,43).…”
Section: Discussionmentioning
confidence: 95%
“…The R482 residue might, directly or indirectly, play a role in the coupling between energy supply and drug transport, and this effect would be altered upon mutation. A comparable activation or inhibition of ATP hydrolysis by modulators has been often reported for P-glycoprotein (42) and MRP1 (17,43).…”
Section: Discussionmentioning
confidence: 95%
“…The vanadate-sensitive ATPase activity of the multidrug transporter MDR1 has been shown to reflect the substrate interactions of this protein: transported substrates significantly (up to 3-to 6-fold compared with the baseline level) stimulated the ATPase activity, whereas non MDR1 substrates had no effect (see Sarkadi et al, 1992;Scarborough, 1995). In one study, Chang et al (1998) examined the vanadate-sensitive ATPase of the purified MRP1 protein and found stimulation by GS conjugates, although stimulation was weak (1.3-to 1.5-fold). In the present experiments, by using the high-level expression of human MRP1 and MRP2 in Sf9 cells, we examined the effects of various compounds on the ATPase activity of both proteins in a membrane environment.…”
Section: Resultsmentioning
confidence: 99%
“…To date, this has not been demonstrated. Although the K ATP channel has a relatively slow rate of ATP hydrolysis (100 nmol Pi min K1 mg K1 protein; Mikhailov et al 2005) compared with other ABC proteins, it nevertheless lies within the range of that reported for MRP1 (from 5 to 470 nmol Pi min K1 mg K1 protein; Chang et al 1998;Mao et al 1999). Thus, it is not inconceivable that it serves as a transporter of an as yet unidentified substrate.There is accumulating evidence, however, that SUR1 also plays a role in insulin granule exocytosis.…”
Section: Conclusion and Future Challengesmentioning
confidence: 93%